1978
DOI: 10.1042/bj1760977
|View full text |Cite
|
Sign up to set email alerts
|

Conversion between renin and high-molecular-weight renin in the dog

Abstract: Two forms of renin, one of mol.wt. 43,000 and the other 60,000, were found in the dog kidney. Conversion between the two forms of renin was reversible at neutral pH. Though the molecular weight of renin in kidney-cortex homogenate was 43,000, it was completely converted into high-molecular-weight renin in the presence of substances that react with thiol groups. On the contrary, stored renin in the granules was the form of normal size (mol. wt. 43,000) regardless of the absence or presence of such substances. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
14
0

Year Published

1980
1980
2005
2005

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(20 citation statements)
references
References 14 publications
6
14
0
Order By: Relevance
“…21 These data have been supported by findings of other investigators. 22 However, Kawamura et al 23 more recently found a small amount of inactive renin in the dog kidney.…”
Section: Discussionsupporting
confidence: 82%
“…21 These data have been supported by findings of other investigators. 22 However, Kawamura et al 23 more recently found a small amount of inactive renin in the dog kidney.…”
Section: Discussionsupporting
confidence: 82%
“…Sagnella et al [17] and our group [22] have indicated that renin stored in renin granules of rat kidney could not be activated by acidification. Funakawa et al [23] also reported similar findings using dog kidney extract. On the other hand.…”
Section: Discussionsupporting
confidence: 71%
“…3). Renin from granular structures of the dog 27 also displayed a MW of about 40,000, indicating that in these species the storage form of renin is of the LMW type. In the present studies, the possibility of proteolytic conversion of renin by enzymes from other subcellular organelles was minimized by the rapid isolation of subcellular organelles and the subsequent osmotic lysis at 0°C before gel filtration on Sephadex G-100.…”
Section: Effect Of N-ethylmaleimlde On Gel Filtration Of Renin From Smentioning
confidence: 99%